(untitled) (Indian Journal of Arid Horticulture, 2018)
Agriculture supply is uncertain and this leads to fluctuations in prices. The study investigates the price details, market integration of ragi in selected markets of Tamil Nadu and Karnataka. The time series data of ragi in wholesale prices were collected for 15 years for the time period of 2003-2017. The results from the analysis of price variations, the seasonal indices of ragi are found to be higher in sowing months and the ragi price trend showing more fluctuation, as the consumption pattern of ragi has widened and demand for Ragi is increasing the years. The unit root test revealed that the four wholesale markets except Vellore market were non stationary at 1 per cent level and become stationary after first differencing. In Johansen co-integration procedure there is three co-integration equations at 5 per cent level of significance among the ragi prices. The VECM estimates in short-run Chintamani market price converged into equilibrium within 6 days. The shock observed by the Tumkur market price will be corrected within 10 days. In the long-run Chintamani and Tumkur markets were influenced by their own monthly lagged price and Hosur markets were influenced by Denkanikottai first month lagged prices of the market.